2013
DOI: 10.1016/j.ijforecast.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying survey expectations: What’s wrong with the probability approach?

Abstract: Provided in Cooperation with Quantifying survey expectations:What's wrong with the probability approach? AbstractWe study a matched sample of individual stock market forecasts consisting of both qualitative and quantitative forecasts. This allows us to test for the quality of forecast quantification methods by comparing quantified qualitative forecasts with actual quantitative forecasts. Focusing mainly on the widely used quantification framework advocated by Carlson and Parkin (1975), the so-called "probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…By means of simulation-based expectations, Löffler (1999) and Terai (2009) Breitung and Schmeling (2013) corroborated the importance of introducing asymmetric and dynamic indifference parameters, but found that individual heterogeneity across respondents plays a minor role in forecast accuracy. On the other hand, Lahiri and Zhao (2015) have recently found strong evidence against the threshold constancy, symmetry, homogeneity, and overall unbiasedness assumptions of the probability method.…”
Section: Quantification Of Qualitative Survey Datamentioning
confidence: 74%
“…By means of simulation-based expectations, Löffler (1999) and Terai (2009) Breitung and Schmeling (2013) corroborated the importance of introducing asymmetric and dynamic indifference parameters, but found that individual heterogeneity across respondents plays a minor role in forecast accuracy. On the other hand, Lahiri and Zhao (2015) have recently found strong evidence against the threshold constancy, symmetry, homogeneity, and overall unbiasedness assumptions of the probability method.…”
Section: Quantification Of Qualitative Survey Datamentioning
confidence: 74%
“…Abberger (2007) uses probit analysis to estimate a quantitative threshold for employment expectations that allows to differentiate between a decrease and an increase in actual employment. Several refinements of the probabilistic approach have been proposed in order to reduce the measurement error introduced by restrictive assumptions (Lahiri and Zhao, 2015;Breitung and Schmeling, 2013;Łyziak, 2013;Müller, 2010;Mitchell, Mouraditis and Weale, 2007;Claveria et al, 2003Claveria et al, , 2006Weale, 2002, 2005;Löffler, 1999;Berk, 1999;Smith and McAleer, 1995;Dasgupta and Lahiri, 1992;Kariya, 1990;Batchelor and Orr, 1988;Seitz, 1988;Batchelor, 1986;Toyoda, 1979). states by means of panel vector autoregressive models, finding no significant differences in both groups.…”
Section: Literature Review On the Quantification Of Survey-based Expementioning
confidence: 99%
“…Carlson and Parkin (1975) applied the method by using a normal distribution together with symmetric and constant threshold parameters across respondents and over time. Extensions of this framework are mainly focused on reducing the measurement error introduced by incorrect assumptions (Lahiri and Zhao 2015;Breitung and Schmeling 2013;Mitchell et al 2002;Löffler 1999;Berk 1999;Smith and McAleer 1995;Dasgupta and Lahiri 1992;Kariya 1990;Batchelor and Orr 1988;Seitz, 1987;Pesaran 1984;Batchelor 1982Batchelor , 1986Toyoda 1979). By means of Monte Carlo simulations, Terai (2009) andLöffler (1999) Matching firm-level responses to quantitative realizations, several authors have also developed extensions of the probability approach.…”
Section: Introductionmentioning
confidence: 99%